Application of Computational Modeling for Explosive Hazard Assessments. Issue 3 (September 2013) - Clutter, J. Keith
Computational modeling is routinely used in the design and development of explosive systems but is not typically applied in performing hazard assessments related to explosives. Typically simplified models are used to perform analysis related to safety and security applications involving explosives. These models can misrepresent the destructive output from explosive devices because they do not resolve many of the aspects of the scenarios such as wave reflection, channeling and focusing of blast waves. Here a computational model developed specifically for explosive hazard assessments is reviewed and the advantages as compared to simple models are highlighted. Some of the obstacle to applying computational modeling to routine explosive hazard assessment problems is the ability to perform analysis in a timely manner and address the wide range of explosives encountered. Here techniques being developed to increase flexibility in application and increase efficiency are presented.